The Effect of Kind of Cutting and Planting Position on Germination and Early Growth of Sugar Cane (Saccharum officinarum L.) Seedlings - Quiko Andreas, Prapto Yudono, dan Rohlan Rogomulyo (Vegetalika, 2013)
ABSTRACTThis study aimed to determine the effect of kinds of cutting which planted in vertical, horizontal and diagonal position to the germination, early seedling growth. This was a field research, at field laboratorium, Tridharma, Banguntapan, Bantul, Faculty of Agriculture, Gadjah Mada University, Yogyakarta in October to December 2012.This study used a factorial experimental design 2 x 3 plus 1 control, with a Completely Randomized Design (CRD) 4 replications. The first factor was the kinds of cutting consisting of 3 levels i.e bagal, budchip and budset. The second factor was the position at planted consisting 3 levels i.e vertical, incline and horizontal with the bud facing up. The collected data were analyzed by using analysis of variance (Anova) applying level of significance at α = 5%. When significant differences among treatments were found, further analysis was carried out by applying a Least Significant Difference test (LSD) at α = 5%. The results showed that there are significant interactions between treatments of kind of cutting and planting position affect percent germination, canopy dry weight in 9 week after planting (wap), root dry weight 9 wap and growth rate in 6-9 wap. Kinds of cutting and planting positions significantly increases the plant height, leaf number, tiller number, stem diameter, fresh canopy weight of 12 wap, canopy dry weight in 12 wap, Net Assimilation Ratio (NAR) 9-12 wap, Crop Growth Rate (CGR) in 9-12 wap. Combination of budchip planted horizontal (89%) and vertical (87%) position showed the best combination germination percentage. Keywords: Kind of cutting, sugar cane, planting position